International cooperation in the sphere of peaceful uses of nuclear energy as a resolution of energy supply and nuclear proliferation problems - M. V. Zharkih (MGIMO University Press, 2009)
Comparative analysis of the Russian and the US initiatives. The article gives an outline of such a promising branch of international cooperation as cooperation in the sphere of peaceful uses of nuclear energy, in particularly its multilateral aspects – initiatives of States based on the multilateral principle of uses of nuclear power. The comparative analysis of the two large-scale initiatives in the field ofmultilateral approaches to the nuclear fuel cycle – these are the Russian initiative on the development of the Global infrastructure of nuclear energy and the American Global nuclear energy partnership –made in the article discloses the main principles of work of the abovementioned mechanisms of interaction as well as their advantages and disadvantages. The goal of such an analysis is to figure out which one has a greater potential for international security and future development of the nuclear energy sector.